Partial Implementation of the Folded Line Equivalent Transmission Line Model in the ATP version of the Electromagnetic Transients Program - Colqui, Jaimis S. L. [UNESP]; Timana, Luis; Torrez, Pablo [UNESP]; Kurokawa, Sergio [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2021)
The Folded Line Equivalent (FLE) is a transmission line model that decomposes the nodal admittance matrix of the transmission line into an open-circuit admittance matrix and a short-circuit admittance matrix. The resulting admittance matrices are then fitted to rational functions and associated with equivalent electrical circuits. Technical literature suggests that the FLE can be implemented in EMTP-like software, but no paper had proposed a method to implement it in the ATP-EMTP. This paper proposes a new representation of the FLE, which can be implemented in the ATP-EMTP. We propose to use an orthonormal matrix instead of the matrix proposed by the authors of the FLE. The proposed approach can represent short lines in simulations with time steps greater or equal to the propagation time of the transmission line. We compare the results obtained with the proposed approach to the JMarti model and the Universal Line Model. Results show that the proposed approach is accurate and is less sensitive to the time step used in the simulations.
Keywords: electromagnetic transients; nodal admittance matrix; rational fitting; transmission line